LA VUELTA AL MUNDO DE LA LINTERNA MÁGICA EN OCHENTA VISTAS1 - Francisco Javier FRUTOS ESTEBAN,Carmen López SAN SEGUNDO (Fonseca, Journal of Communication, 2023)
Although the magic lantern developed a prosperous equipment industry and satisfied a varied consumer demand based on the development of very sensible expressive systems, its study has been left out of the academic curriculum in the history of mass media